Profitability Analysis of Audit Firms – Evidence from the Republic of Serbia - Kristina Mijić; Dijana Rao (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
This paper aims to provide an analysis of the profitability of audit firms in the Republic of Serbia during the period 2016-2018. The analysis is based on the data collected from the financial statements from all audit firms registered in the Republic of Serbia. The profitability analysis includes two goals. This paper will primarily provide a descriptive statistical analysis of the profitability of audit firms measured by return on assets and net income per employee. The following part of the research will answer the question of which factors have a significant impact on the profitability of audit firms. Profitability as a dependent variable is defined as return on assets and net income per employee, while independent variables include market share, current ratio, leverage, size, affiliation to the international network, etc. To answer this question, a regression statistics analysis will be conducted. The research result will indicate which factor can improve the performances of audit firms.
Keywords: M42; 330; audit firm; profitability; financial statement